Faith, Ecology, and Frugality: Unpacking Muslim Consumers’ Motivations Toward Fashion Thrifting - Widyaningsih, Meilana; Priyanka, Felyna; Bibi, Safia (Relevance: Journal of Management and Business, 2025)
This study unpacks the intertwined motivations of faith, ecological consciousness, and frugality that shape fashion thrifting behavior among Muslim consumers in urban Indonesia. Anchored in Self-Determination Theory (SDT) and the Theory of Planned Behavior (TPB), the research constructs a model that traces how intrinsic motivations (religiosity and environmental awareness) and extrinsic motivation (frugality) inform attitude, subjective norms, perceived behavioral control, and actual thrifting behavior. Differing from previous fragmented approaches, this model’s originality lies in its holistic integration of spiritual and economic drivers within a single structural framework to explain value-laden consumption. Using a cross-sectional survey and SEM-PLS analysis on 194 respondents, the study reveals that attitude serves as the central conduit for these motivations. Frugality emerges as the most consistent direct predictor, while religiosity and ecological awareness exert nuanced indirect influences. Multi-group analysis highlights gender as a significant moderator, whereas generational differences are less pronounced. Practically, these findings suggest that thrift industries should adopt gender-specific marketing that aligns with Islamic ethical values, while policymakers can leverage these spiritual-ecological links to promote sustainable consumption in emerging markets.